Dampak digitalisasi terhadap ekonomi bisnis - Faizal, Akhmad Nur (Maliki Interdisciplinary Journal, 2024)
The development of digital technology has brought significant changes in various sectors of the economy in Indonesia, including the halal industry, SMEs, and tourism. Digitalization changes the way operate, increases efficiency, and creates new opportunities for innovation and growth. Digital transformation in halal industries improves operational efficiency and service quality, while digital marketing helps SMEs increase visibility and sales. Indonesia’s digital economy is growing rapidly with the growth of e-commerce, digital payments, and online services, which also have a positive impact on the tourism sector. However, digitalization also brings challenges, such as cybersecurity risks, digital gaps, job relocation, technology dependence, and privacy issues. To overcome these challenges, need to invest in cyber security, provide sustainable training, diversify digital tools, promote digital inclusion, embrace innovation, and comply with data privacy regulations. With the right adaptation strategies, can leverage the digital age to growth and sustainability in an increasingly connected global economy.